2022
DOI: 10.3389/fnut.2022.961679
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysable tannins, physicochemical properties, and antioxidant property of wild-harvested Terminalia ferdinandiana (exell) fruit at different maturity stages

Abstract: Terminalia ferdinandiana Exell., also known as Kakadu plum, is a wild-harvested native Australian fruit with limited information on how maturity is affecting the phytonutritional properties and bioactivities of the fruit. Thus, this study investigated changes in hydrolysable tannins, phenolic acids, sugar profile, standard physicochemical parameters, and antioxidant-scavenging capacity of wild-harvested Kakadu plum fruits at four different maturity stages, from immature to fully mature. Fruits harvested &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similar trends have been observed in many other fruits, e.g., plum [38], bilberry [39], blackberry [34], or blueberry [27]. According to the literature, the value of TSS is positively correlated with sugar accumulation and it can be used as a marker of fruit maturity [40].…”
Section: Total Soluble Solidssupporting
confidence: 78%
“…Similar trends have been observed in many other fruits, e.g., plum [38], bilberry [39], blackberry [34], or blueberry [27]. According to the literature, the value of TSS is positively correlated with sugar accumulation and it can be used as a marker of fruit maturity [40].…”
Section: Total Soluble Solidssupporting
confidence: 78%
“…The concentration of organic acids is the result of organic acid synthesis, catabolism and tissue storage [ 49 ]. The increase in TA in some fruit samples may be caused by a ‘simple’ concentration effect due to the moisture loss of the samples during ambient storage [ 50 ], and/or a change in the respiratory metabolism, leading to an increased TA [ 51 ], and/or the inherent variation in the wild harvested fruits [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al (2023) reported that goji berry contains the highest number of flavonoids when it is a green fruit, but as it matures, the content of flavonoids decreases [37]. Phan et al (2022) reported that total soluble solid and titratable acidity increased depending on the ripening stage of Kakadu plum fruits, but the content of phenolic compounds, including tannin, tended to decrease [38]. In addition, our previous study [39] showed that the content of active compounds in the fruit of Cudrania tricspidata decreases as the size of the fruit increases.…”
Section: Discussionmentioning
confidence: 99%